Incidence of and factors associated with SARS‐CoV‐2 infection among people living with HIV in Southern Spain after one year of pandemic. Issue 4 (4th September 2021) - Fernandez‐Fuertes, Marta; Corma‐Gomez, Anaïs; Torres, Eva; Rodriguez‐Pineda, Elena; Fuentes‐Lopez, Ana; Rincon, Pilar; Fernandez, Nieves; Garcia, Federico; Bernal, Samuel; Real, Luis M.; Macias, Juan; Pineda, Juan A.
Abstract: Whether people living with HIV (PLWH) are at greater risk of acquiring SARS‐CoV‐2 infection is currently unknown. Prospective serologic studies may allow seroincidence analyses, where all infections are accurately identified. Because of this, we evaluated the incidence of associated factors with and the clinical outcome of SARS‐CoV‐2 infection in PLWH in Southern Spain. This prospective cohort study included PLWH from a Tertiary University Hospital in Southern Spain. Patients were enrolled in the study if (1) they had attended as outpatients our Unit from 1 August 2019 to 8 February 2020 and (2) had two subsequent evaluations from 9 February 2020 to 4 March 2021. SARS‐CoV‐2 infections were diagnosed by PCR, antigen detection or serology. Seven hundred and nine PLWH were included in the study. Of them, 55 [7.8%, 95% confidence interval (95% CI) 5.9%–9.9%] patients developed SARS‐CoV‐2 infection. Between 18 May and 29 November 2020, the rate of seroconversion was 5.3% (95% CI: 3.1%–9.0%) for the general population in the area of Seville and 2.3% (95% CI: 1.3%–2.6%) for PLWH in this study ( p  = .001). After multivariable analysis, adjusted by age, sex, and risk factors for HIV infection, active tobacco use and CDC stage, active tobacco smoking was the only factor independently associated with lower risk of SARS‐Cov‐2 infection [Incidence rate ratio: 0.29 (95% CI 0.16–0.55) p  < .001]. In conclusion, the incidence of SARS‐CoV‐2 infection among PLWH in Southern Spain during the ongoing pandemic was lower than that reported for the general population in the same area.